Pemanfaatan Aplikasi Pianika Sebagai Media Pembelajaran Seni Musik di SMP Negeri 2 Tomohon - Meyny S.C. Kaunang; Luccylle Manina Takalumang; Madinah Putri Saptono (Musica: Journal of Music, 2026)
This study aims to describe the use of a pianica application as a music learning medium at SMP Negeri 2 Tomohon. The study is grounded in the need for innovative learning media that can support students’ musical practice amid limited classroom time and the availability of physical musical instruments. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of a cultural arts teacher and eighth-grade students involved in music learning activities. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings show that the pianica application functions as an interactive audio-visual medium that helps students recognize the arrangement of notes, connect musical notation with sound, and practice finger coordination more independently. The application also encourages students’ learning motivation and participation because the learning process becomes more engaging, practical, and accessible. However, its use still requires teacher guidance, especially for students who are not yet familiar with digital music applications or who have limited access to personal devices. Thus, the pianica application can be used as an alternative digital learning medium to support music learning at the junior high school level.